Strategi Pengembangan Produk Event Untuk Menarik Minat Pelanggan di Phenom Indonesia pada Masa Pndemi Covid-19 - Ni Nyoman Ayuning Suryawati; Luh Putu Citrawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2022)
The purpose of this study was to determine the Event Product Development Strategy as an effort to increase sales and attract customer interest at Phenom Event Indonesia during the Covid-19 pandemic. The theory used is the business model canvas theory which consists of 9 elements, namely: Customer Segment, Value proposition, Channels, Customer relationship, Revenue stream, Source resources (Key Resources), Key activities (Key activities), Partnership (key partners), and financial structure (Cost structure) followed by a SWOT analysis. From the results of the study, it is known that there are several product development strategies carried out by Phenom Event Indonesia. These strategies are (1) creating the first virtual studio in Bali, (2) maintaining communication with customers, (3) collaborating with vendors, (4) updating more sophisticated virtual event equipment, (5) increasing HR competence in the virtual event field., (6) optimizing promotions using social media Tiktok, Youtube and Instagram